Cardiac Beriberi: Two Modes of Presentation. Issue 5774 (4th September 1971) - McIntyre, Neil; Stanley, Nigel N.
Abstract : Two patients suffering from cardiovascular beriberi presented with different clinical manifestations. One had the classical features of a high cardiac output with raised jugular venous pressure and gross oedema. The other was in fulminating heart failure with clinical evidence of a low cardiac output but no peripheral oedema. The latter type of beriberi (shoshin) is rare. Cardiovascular beriberi has a high mortality when untreated. Both patients responded dramatically to thiamine, and this emphasizes the importance of considering thiamine deficiency as a cause of heart failure even when the cardiac output is low.